Skeletal ossification of Middle Triassic pachypleurosaur Keichousaurus hui (Reptilia: Sauropterygia) revealed by zinc distribution - Wang,Yi-nuo; Jiang,Da-yong; Motani,Ryosuke; Yao,Ming-tao; Ji,Cheng; Sun,Zuo-yu; Zhou,Min (PeerJ, 2025)
The elemental composition of seven specimens of Keichousaurus hui, a small pachypleurosaur from the Middle Triassic of China, was analyzed via Micro X-ray fluorescence (Micro-XRF). The results indicate that the distribution of zinc (Zn) is notably correlated with the bones of the skeletons and preferentially enriched in certain areas, unlike other bone-enriched elements such as calcium (Ca), phosphorus (P), and strontium (Sr). Based on the distribution of Zn and its chemical properties, Zn is interpreted as a potential indicator of active ossification in K. hui. A comparative analysis of juvenile and subadult specimens reveals distinct patterns of Zn enrichment, reflecting differential bone development across ontogenetic stages. Notably, the Zn distribution in the subadult specimen of K. hui suggests the ossification of the tarsals gradually progresses from the centre to the periphery of each tarsal bone, which is consistent with typical endochondral ossification observed in extant reptiles. Furthermore, by integrating morphological features with the Zn distribution patterns, we infer that pachyostosis in K. hui develops progressively across all stages of growth and development.
Keywords: Triassic; Micro-XRF; Pachypleurosaur; Ossification; Zinc